Game-Oriented Problem Exploration (GOPE) Model in Language Learning: A Teacher’s View - Vivi Indriyani; Herlin Triana; Anisa Nurjanah; Delsy Arma Putri (STAI Hubbulwathan Duri, 2024)
The development of students' critical and collaborative thinking skills is essential, particularly in Indonesian language learning. To address this, a targeted learning model is needed. The Game-Oriented Problem-Based Learning and Engagement (GOPE) model has been proposed, but a needs analysis is required to assess its feasibility and integration into classroom settings. A descriptive survey method was employed to analyze teacher needs for the GOPE model in Indonesian language learning. Data were collected through questionnaires administered to Indonesian language teachers across various schools. The responses were analyzed using a descriptive quantitative approach to identify patterns and trends in teachers' perspectives. Findings revealed that teachers recognized the critical role of integrating problem-based learning and gaming elements to enhance student engagement and motivation. Most participants emphasized that such integration could significantly improve learning outcomes and foster students' critical and collaborative thinking skills. The data supported the hypothesis that the GOPE model could address these educational challenges effectively. The results suggest that the GOPE model has potential as an innovative tool in language learning. Its emphasis on combining problem-solving strategies with interactive gaming aligns with teachers’ views on effective pedagogical practices. Further research and development are recommended to optimize its application and assess its impact on students’ skills and learning achievements. This study highlights the need for innovative learning models in Indonesian language education. The GOPE model shows promise in enhancing critical and collaborative skills, suggesting a positive step toward improved educational practices.